Aspek-Aspek Sistim Pengendalian Internal Dalam Peningkatan Pengawasan di Inspektorat Daerah Kabupaten Bolaang Mongondow Utara - Pontoh, Rachmat Ravid; Rantung, V. V.; Pesoth, Welly (JURNAL ILMIAH SOCIETY, 2015)
Government Internal Supervisory authorities in this case the Regional Inspectorate Bolaang North Mongondow in the implementation of the internal control system as an effort on the implementation of control policies have been carrying out their duties in accordance with what is expected. This research using qualitative methods aims to identify and analyze implementasikebijakan supervision over the implementation of internal control which is expected to contribute ideas to the concept of local government control policies for the improvement of government services and community development.Results of the study revealed that the aspects of the system of internal control is a factor that can help control policy implementation as the problems that occur when the Government Internal Supervisory Apparatus Regional Inspectorate conducting oversight of all programs and activities of local governments in the course of the duties and functions of local work unit funded by the local budget. In fact the Regional Inspectorate is one of oversight institutions whose activities are carried out in the scope of his agency alone, the success of internal control is predicated not only on the design of adequate controls to ensure the achievement of organizational goals but also to everyone in the organization to take fairness and propriety, and considering the size , complexity, and nature of the duties and functions of government agencies with regard to the five main aspects, namely internal control: control environment, risk assessment, control activities, information and communication, and monitoring.Keywords: System, Control, Supervision.